O uso consciente da água para a sustentabilidade: uma abordagem de aprendizagem interdisciplinar no ambiente escolar. - SANTANA, Diego Rodrigues (Universidade Federal do Pará, 2024)
Environmental issues have gained notoriety in the social context, as the impacts continuously caused by human action have directly affected terrestrial and aquatic ecosystems. The present work aimed to research the importance of water, conscious consumption and wasting water at Coronel Sampaio Municipal Elementary School, from 6th to 9th grade. The methodological instruments used were learning based on the problematization methodology of Charles de Maguerez, with contributions from participant-action-research and project-based learning methodology. It was developed in three stages: initially discussing the importance of water as an essential element for quality of life, through the school project “We need to talk about water”, with interdisciplinary lectures and lectures. The present study culminated in an educational product, a Board Game, as a ludic and pedagogical instrument with the objective of assisting the teaching practice in relation to the contents of the curricular components that involve the theme “water” according to the BNCC. The results of this educational product obtained through the evaluation made by students and teachers were positive and with benefits that favor the pedagogical practice and can be consulted at the end of this work.